Threshold criteria for incipient grain motion with turbulent fluctuations on a horizontal bed - Wan Mohtar, W.H.M. (Universiti Kebangsaan Malaysia, 2015)
The effect of turbulent fluctuations on the threshold criteria for incipient grain motion over a wide range of sediment size is investigated. In this work, attention is paid to the comparison of the critical Shields parameter θc profile obtained when the near-bed fluid forces induced sediment motion are oscillating-grid turbulence and a single idealised eddy of vortex ring. For experimental work, near-spherical monodisperse sediments were used throughout with relative densities of 1.2 and 2.5 and mean diameters d ranging between 80 and 1087 μm. The measured values of θc on a horizontal bed α = 0 (hence denoted as θc0), were compared to the θc0 profiles obtained by grid turbulence and vortex ring experiments. Although different in magnitude, the θc0 profiles were comparable, that is the θc0 were seen to increase monotonically for hydraulically smooth bedforms and to be approximately constant for hydraulically rough bedforms. However the limit of hydraulically smooth region was found to vary between the oscillating-grid turbulence experiments, where wider smooth region was found when the turbulent fluctuations used to calculate θc0 is not the near-bed velocity.